(untitled) (Журнал «Маркетинг», 2025)
This article analyzes the existing problems in the road transport services market of the Republic of Uzbekistan, particularly in the field of freight forwarding services. To address these issues, special attention is given to the development of a concept aimed at ensuring the effective functioning of this market. The proposed concept includes both theoretical foundations and practical recommendations designed to fundamentally change the approach to freight forwarding services.